Comparison between flux estimation methods for direct torque controlled permanent magnet synchronous motors - Shady M. Sadek; Mostafa H. Mostafa; Ahmed K. Ryad (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
Nowadays, direct torque control (DTC) of AC drives is one of the most interesting fast dynamic response motor control techniques. Permanent magnet synchronous motors (PMSM) are now replacing induction motors (IM) in a wide range of applications because of their salient merits such as high efficiency and compactness. Combining DTC and PMSM in one drive may result in excellent performance not only for torque dynamics but also for efficiency. DTC relies on the estimation of the stator flux and torque to be compared with the set points of the torque and flux. In the literature, there are various flux estimation methods and each one has its own merits and demerits. Comparisons of these various methods are discussed in this paper showing their effect on the drive performance through MATLAB/Simulink simulations.